2013
DOI: 10.1152/ajpcell.00174.2012
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous modification of platelet membranes with the omega-3 fatty acids EPA and DHA reduces platelet procoagulant activity and thrombus formation

Abstract: Several studies have implicated the omega-3 fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) in inhibition of normal platelet function, suggesting a role for platelets in EPA- and DHA-mediated cardioprotection. However, it is unclear whether the cardioprotective mechanisms arise from alterations to platelet-platelet, platelet-matrix, or platelet-coagulation factor interactions. Our previous results led us to hypothesize that EPA and DHA alter the ability of platelets to catalyze the gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 34 publications
2
41
0
Order By: Relevance
“…Very recent studies have suggested that exogenous modification of platelet membranes by omega-3 fatty acids results in decreased platelet procoagulant activity and thrombus formation. 22 Platelets show less aggregation and activation in healthy subjects who are taking omega-3 supplements. 23 Population-based studies suggest that for an association with lower fibrinogen levels to be seen, fish oil consumption must be high, achieving red blood cell levels similar to those seen on pharmacologic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Very recent studies have suggested that exogenous modification of platelet membranes by omega-3 fatty acids results in decreased platelet procoagulant activity and thrombus formation. 22 Platelets show less aggregation and activation in healthy subjects who are taking omega-3 supplements. 23 Population-based studies suggest that for an association with lower fibrinogen levels to be seen, fish oil consumption must be high, achieving red blood cell levels similar to those seen on pharmacologic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Potential mechanisms whereby omega-3 PUFAs may regulate dopamine include reducing cortical MAO-B activity, thereby decreasing the degradation of monoamines (Chalon et al, 1998); improving dopamine neuron survival (Ahmad et al, 2008); and influencing lipid rafts (Rockett et al, 2011; Rockett et al, 2012; Williams et al, 2012; Larson et al, 2013), that, in turn, may upregulate D1 receptors (Yu et al, 2004) and mediate D2 receptor endocytosis (Genedani et al, 2005). …”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory effect of O3FA on pro-coagulant platelet- and monocyte-derived microparticles has also been described in specific situations 21,22 . Additionally, EPA and DHA can decrease platelet-mediated thrombin generation, thereby acting indirectly on the coagulation cascade 23 . O3FA are also known to potentiate plasma fibrinolysis by increasing the levels of vascular plasminogen activator and reducing the levels of its inhibitors 24 .…”
Section: Discussionmentioning
confidence: 99%